Leg extension strength, explosive strength, muscle activation, and growth as predictors of vertical jump performance in youth athletes - Gillen, Z. M.; Shoemaker, M. E.; McKay, B. D.; Bohannon, N. A.; Gibson, S. M.; Cramer, J. T. (Journal of Science in Sport and Exercise, 2020)
Purpose: The purpose of this study was to examine the relationships among leg extension strength, explosive strength, muscle activation, and measurements of growth to predictions of vertical jump performance in youth athletes. Methods: Height, body mass, skinfolds, and quadriceps femoris muscle cross-sectional area were measured in 39 sports active children (20 females, 19 males, age = 12.52 ± 0.62 years old). Peak torque (PT), rate of torque development (RTD), rate of velocity development (RVD), and rate of electromyographic amplitude rise (RER) were measured during isometric and isokinetic leg extensions. PT, RTD, and RVD were expressed in absolute terms and normalized to body mass. Estimated jump height (JH) and peak power (PP) were assessed during static (SJ), counter-movement (CMJ), and drop (DJ) jumps. Results: JH exhibited greater correlations with PT normalized to body mass (r = 0.387-0.758) than absolute PT (r = 0.338-0.417), whereas PP exhibited greater correlations with absolute PT (r = 0.368-0.837). Only negligible to moderate relationships existed between JH and PP across all jumps (r = 0.053-0.605). Over 50% of the variability in PP was predicted in 24 of 30 regression models with absolute muscle strength, muscle activation, and measurements of growth, while only 6 of 30 models predicted more than 50% of the variability in JH. Conclusion: Overall, absolute static and dynamic muscle strength, muscle activation, and growth better explained PP measured during vertical jumps than estimated JH.